2021
DOI: 10.3390/life12010036
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Progression Biomarkers of Early and Intermediate Age-Related Macular Degeneration

Abstract: Early and intermediate AMD patients represent a heterogeneous population with an important but variable risk of progression to more advanced stages of the disease. The five-year progression from early and intermediate AMD to late disease is known to range from 0.4% to 53%. This wide variation explains the particular interest in searching predictive AMD biomarkers. Clinical parameters such as drusen size, presence of pigmentary abnormalities, and fellow eye status were, traditionally, the more important predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 72 publications
(129 reference statements)
0
15
0
Order By: Relevance
“…While risk factors for AMD have been well defined ( 1 , 11 , 45 , 46 ), they are also multifactorial in nature, creating a level of complexity in both disease diagnosis and intervention/treatment strategies. Further complicating diagnostic accuracies, early pathological signs, including small yellow lipid-filled deposits under the retina called drusen, as well as pigmentary abnormalities, can only be used to indicate the potential risk of AMD development, as they can also be found within the healthy aging population ( 1 , 6 , 12 , 47 , 48 ). Therefore, for those at risk, currently the only intervention strategy to combat AMD progression is dietary supplementation of AREDS2 formulation multivitamins, however this remains only efficacious in slowing the progression from intermediate to late-stage AMD ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…While risk factors for AMD have been well defined ( 1 , 11 , 45 , 46 ), they are also multifactorial in nature, creating a level of complexity in both disease diagnosis and intervention/treatment strategies. Further complicating diagnostic accuracies, early pathological signs, including small yellow lipid-filled deposits under the retina called drusen, as well as pigmentary abnormalities, can only be used to indicate the potential risk of AMD development, as they can also be found within the healthy aging population ( 1 , 6 , 12 , 47 , 48 ). Therefore, for those at risk, currently the only intervention strategy to combat AMD progression is dietary supplementation of AREDS2 formulation multivitamins, however this remains only efficacious in slowing the progression from intermediate to late-stage AMD ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…57 Furthermore, Flores et al identified iRORA as the factor with the higher probability of developing advanced AMD (OR 12.91). 58…”
Section: Atrophic Changesmentioning
confidence: 99%
“…Events that are pathologic take place when external pressures overcome equilibrium. Although anti-angiogenic therapies that block the bioactivity of vascular endothelial growth factor (anti-VEGF) have changed results in nAMD, over 50% of patients still lose their eyesight after therapy [22]. Only the exudative types of the condition are now treatable, and the medication used does so by blocking vascular endothelial growth factor (VEGF).…”
Section: Neovascular Age-related Macular Degenerationmentioning
confidence: 99%